The construction, reliability, and evidence of validity of a scale to measure new technologies by Spanish psychologist - Ramos-Álvarez, Rodolfo; Sánchez-Martín, Milagrosa; Rodríguez-Ruiz, Mª-Mercedes; Fausor, Rocío (Anales de Psicología / Annals of Psychology, 2023)
In this study we present the construction and analysis of a questionnaire for analyze the use of new technologies (NNTT) by psychology professionals, based on a sample of 1759 psychologists.). The final version composed by 36 items was generated from a bibliographic review on the new technologies applied to psychology. Exploratory factor analysis of selected items based on a randomized sample (n = 853) indicated the presence of five factors related to 1.- Online storage; 2.- Use of basic office and internet tools; 3.- Communication routes with the patient; 4.- Basic and advanced knowledge of programming and evaluation languages; 5.- Psychological interventions through NNTT. Validity of the 5-factor structure was supported by confirmatory factor analysis carried out with the remaining sample (n = 906). The results of reliability (internal consistency) and validity were adequate. Significant differences are found by sex, men obtain higher scores in both factor 1 and 3. The developed questionnaire is a valid and reliable instrument to measure the proposed construct.